Holocene relative sea-level history of the Southern Victoria Land Coast, Antarctica - Hall, B. L.; Baroni, C.; Denton, G. H. (Global and Planetary Change, 2004)
More than 130 radiocarbon dates of penguin remains and guano, sealskin, shells, and seaweed from raised beach ridges afford relative sea-level information for southern Victoria Land. A new relative sea-level curve suggests that the final unloading of grounded ice from the coast took place about 6600 C-14 years BP, in keeping with previous estimates of the timing of deglaciation. Since this time, the coast has experienced 32 m of relative sea-level fall at rates ranging from 2 to 15 mm/year, consistent with glacioisostatic rebound. (C) 2004 Elsevier B.V. All rights reserved.
845idTimes Cited:40Cited References Count:25